PENGKAJIAN NYERI CPOT DAN WONG BEKKER PASIEN PENURUNAN KESADARAN - Apriani; Agustina, Rismia; Hafifah, Ifa (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2018)
Pain assessment of unconsciousness patiens who unable to show their pain respon verbally is an important thing to learn. CPOT is an instrument for scoring the pain of patients who couldn’t doing verbal communication, and Wong Bekker is an easier and faster instrument for pain scale prediction. A sistematic pain assessment on critical unconsciousness patients will reduce long of stay and Healthcare-Associated Infections number. Objective for this research were knowing the effectivity of pain assessment used CPOT and Wong Bekker on critical unconsciousness patients in ICU of Ratu Zalecha Hospital Martapura. Analytic observational experimental by cross sectional on 31 responden in ICU of Ratu Zalecha Martapura, used purposive sampling. This experiment in September up October 2017. Based on the experiment that the CPOT was more effective (17.48) than Wong Bekker (12,54). P Value < 0,05 by mann whitney test. Pain assessment used CPOT was better because pain evaluating based on comprehensive behave signs and indicators. Hospitals may doing pain assessmenet used CPOT.